Transformasi Kepemimpinan Digital: Peran Kepala Madrasah dalam Meningkatkan Efektivitas Pembelajaran di Madrasah Ibtidaiyah - Al Ghifari, Fahmul Hikam; Abidin, Zainal (TARBAWIYAT, 2025)
The rapid development of digital technology has significantly impacted education, demanding innovation in learning systems and school management. The madrasah principal plays a central role in managing and implementing digital strategies to create a more interactive, effective, and efficient learning environment. This research uses a qualitative method with a descriptive approach at MI Al Fattah Banyuurip, Gresik, which has begun adopting technology in its learning process. The findings indicate that the use of digital platforms such as Google Classroom and Zoom increases student engagement in the learning process. The principal also plays a role in enhancing teachers' digital competencies through internal training and the digitalization of madrasah administration, which has proven to simplify attendance recording and student academic data management. However, challenges such as limited infrastructure, low digital literacy, resistance to change, and insufficient policy support remain major obstacles. This study emphasizes that digital leadership can drive innovation in the MI education system if supported by adequate policies, intensive training, and improved technological infrastructure. The study provides strategic recommendations for developing digital education policies in MI and strengthening the role of madrasah principals as innovative leaders in the digital era.